DEVELOPMENT OF A BUSINESS ECOSYSTEM MODEL OF DIGITAL PLATFORMS USING VALUE NETWORK AND BEHAVIORAL ANALYSIS: CASES IN INDONESIA - Siti Dyah Handayani; Fauziyah; Punang Amaripuja; Mohammad Nabil Almunawar; Muhammad Abid Asy Syafiq (Asosiasi Dosen Muda Indonesia, 2026)
With an estimated 171 million internet users from a population of 267 million people in 2019 reported by the Association of Indonesian Internet Providers (APJII, 2019), e-commerce systems have a huge potential to be used as a platform for entrepreneurs. Muhammadiyah University of Yogyakarta has responded to this opportunity by developing the Bedukmutu platform to provide business opportunities for its stakeholders, especially for academic and administrative staff. Bedukmutu has the main objective to manage the economic potential of Muhammadiyah members. The research aims to utilize both the business ecosystem model and the UTAUT (Unified Theory of Acceptance and Use of Technology) theory to analyze the use of Bedukmutu.